Modification of rapeseed straw with organic acid anhydrides. (May 2015) - Paukszta, Dominik; Doczekalska, Beata; Ostrowski, Adam; Bartkowiak, Monika
Modification of lignocellulose materials, used as fillers in the composites with polyolefins, is applied to improve their adhesion to the matrix. One of the most often applied methods of such modification is the treatment with organic acid anhydrides. Rapeseed straw was modified with anhydrides of acetic, maleic and succinic acids. Such a modification changes the straw surface leading to the exposition of the wood tissue skeleton. The character changes depending on the type of anhydride applied. Esterification of repeseed straw by organic acid anhydrides resulted in changes in its chemical structure. According to infrared analysis of modified straw, new carbonyl groups were formed, as indicated by the absorption band in the range 1750–1730 cm −1 . The degree of straw modification, measured by the weight percent gain index, informs about similar reactivities of the lignocelluloses material with all three anhydrides of organic acids used as modifiers. The starting temperatures of active thermolysis for the straw modified with maleic and succinic acid anhydrides were lower than that for native straw, while that for the straw modified with acetic acid was higher. Concentration of free radicals in rapeseed straw samples was measured by electron paramagnetic resonance spectroscopy. It was found that the maximum concentration of radicals for rapeseed straw was treated with maleic anhydride.